Efforts To Reduce Gaps In System And Procedure Irregularities At Ports - Iswanto Iswanto; Ningrum Astriawati; Budi Handojo; Andi Hendrawan (Cita konsultindo, 2023)
The mass of services at ports requires a long bureaucracy that is more like a monopoly or almost dominated by certain parties, which can trigger divergence because users/customers need fast service to avoid a high costing economy, causing loopholes in system and procedure deviations at the Port. This study aims to determine the efforts made to reduce gaps in system and procedure irregularities at the Port. The data collection method is divided into 2 parts, namely: Observation Method and the literature study. The results of the study stated that the efforts that must be made in reducing the gaps in the system and procedure deviations at the Port do the following (1) Equalize the perception of existing systems and procedures, (2) Maximize the National Single Window at ports (3) Monopolies take refuge under bureaucracy, (4) Port Privatization, (5) Five strategies to change bureaucratic behaviour.